2002
DOI: 10.3171/jns.2002.97.supplement_5.0515
|View full text |Cite
|
Sign up to set email alerts
|

Gamma knife radiosurgery for brain metastases: a primary therapeutic option

Abstract: Object. The aim of this retrospective study was to assess the role of gamma knife radiosurgery (GKS) as a primary treatment for brain metastases by evaluating the results in particularly difficult cases such as oncotypes—which are unresponsive to radiation—cystic lesions, and highly critical locations such as the brainstem. Methods. Treatment of 804 patients with 1307 solitary (29%), single (26%), and multiple (45%) brain metastases was evaluated. Treatment planning parameters were as follows: mean tumor volum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
43
0
6

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(53 citation statements)
references
References 38 publications
3
43
0
6
Order By: Relevance
“…In a cohort of patients at our institution who underwent radiosurgery for metastatic brain lesions between 2003 and 2007, we found that the GK is a modality that is efficacious in the treatment of patients with brain metastases, which is similar to previously published reports on the radiosurgical management of these lesions (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28). In our series we found an overall median survival time of 8.5 and 13.7 months from the time of radiosurgery with the GK and initial brain metastasis diagnosis, respectively.…”
Section: Discussionsupporting
confidence: 81%
“…In a cohort of patients at our institution who underwent radiosurgery for metastatic brain lesions between 2003 and 2007, we found that the GK is a modality that is efficacious in the treatment of patients with brain metastases, which is similar to previously published reports on the radiosurgical management of these lesions (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28). In our series we found an overall median survival time of 8.5 and 13.7 months from the time of radiosurgery with the GK and initial brain metastasis diagnosis, respectively.…”
Section: Discussionsupporting
confidence: 81%
“…Radiosurgical treatment of patients with brain metastasis allows a mean survival of 9.6 months, with a 1-year survival rate range of 62% (27) to 77% (22). In the present study, actuarial survival rates at 1 and 2 years were 44.5% and 22.0%, respectively.…”
Section: Survivalmentioning
confidence: 82%
“…Gamma knife therapy holds promise [2] in patients with small-to-medium size (≤ 20 cm 3 ) brain metastases without intracranial hypertension [3]. Results seem to be better than whole-brain radiotherapy and are comparable to surgery combined with radiation [4].…”
Section: Discussionmentioning
confidence: 92%